2015
DOI: 10.1016/j.trc.2014.12.009
|View full text |Cite
|
Sign up to set email alerts
|

A junction-tree based learning algorithm to optimize network wide traffic control: A coordinated multi-agent framework

Abstract: a b s t r a c tThis study develops a novel reinforcement learning algorithm for the challenging coordinated signal control problem. Traffic signals are modeled as intelligent agents interacting with the stochastic traffic environment. The model is built on the framework of coordinated reinforcement learning. The Junction Tree Algorithm (JTA) based reinforcement learning is proposed to obtain an exact inference of the best joint actions for all the coordinated intersections. The algorithm is implemented and tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 31 publications
0
30
0
Order By: Relevance
“…us, it only provides an approximate inference of the exact message being passed. Zhu et al [16] first proposed the JTA instead of the max-plus algorithm to obtain the best joint action for traffic signals and to realize network-wide signal coordination. JTA was first proposed by Jensen et al [17].…”
Section: Review Of the Literature On Signal Coordinationmentioning
confidence: 99%
See 1 more Smart Citation
“…us, it only provides an approximate inference of the exact message being passed. Zhu et al [16] first proposed the JTA instead of the max-plus algorithm to obtain the best joint action for traffic signals and to realize network-wide signal coordination. JTA was first proposed by Jensen et al [17].…”
Section: Review Of the Literature On Signal Coordinationmentioning
confidence: 99%
“…Zhu et al [16] demonstrated that the test network can perform better under the JTA compared to an adaptive or single-agent RLbased control. Although the network system improved, some intersections still experienced poor operations.…”
Section: Motivations and Contributions Of This Studymentioning
confidence: 99%
“…For instance, Zhu et al [19] present a learning algorithm that optimizes traffic control. In particular, their algorithm is executed by means of an ABS.…”
Section: Learning Algorithms In Abssmentioning
confidence: 99%
“…Ella M. Atkins is with the Department of Aerospace Engineering, University of Michigan, Ann Arbor, MI, 48109 USA e-mail: ematkins@umich.edu (see https://aero.engin.umich.edu/people/ella-atkins/). management [4], formation flight [5], and connected vehicle control [6]. Virtual structures [7], [8], consensus [9]- [11], containment control [12]- [14], partial-differential equation (PDE) based approaches [15]- [17], continuum deformation [18], [19], and graph rigidity methods [20], [21] are available multiagent coordination approaches.…”
Section: Introductionmentioning
confidence: 99%